Silent Brain Infarction After Endovascular Arch Procedures: Preliminary Results from the STEP Registry. (February 2021) - Charbonneau, Philippe; Kölbel, Tilo; Rohlffs, Fiona; Eilenberg, Wolf; Planche, Olivier; Bechstein, Matthias; Ristl, Robin; Greenhalgh, Roger; Haulon, Stephan; ,
Abstract : Objective: Few data exist concerning the rate of silent cerebral ischaemic events following endovascular treatment of the aortic arch. The objective of this work was to quantify these lesions using the STEP registry (NCT04489277). Methods: This multicentre retrospective cohort study included consecutive patients treated with an aortic endoprosthesis deployed in Ishimaru zone 0–3 and brain diffusion weighted magnetic resonance imaging (DW-MRI) within seven days following the procedure. DW-MRI was performed to identify the location and number of new silent brain infarctions (SBI). All endografts were carbon dioxide flushed prior to implantation. Results: The study population included 91 patients (mean age, 69 years; men, 64%) from two academic centres treated between September 2018 and January 2020. The procedure was elective in 71 patients (78%). The treatment was performed for a dissection, degenerative aneurysm, or other aortic disease in 44 (49%), 34 (37%), and 13 (14%) patients, respectively. Endografts were deployed in zone 0, 1, 2 or 3 in 23 (25%), 10 (11%), 47 (52%), and 11 (12%) patients, respectively. Endografts were branched (25%), fenestrated (17%), or tubular (58%). At 30 days, there were no deaths or clinical strokes. On cerebral DW-MRI, a total of 245 SBI were identified in 45 patients (50%). Lesions were in the left hemisphere in 63% of the patients (153/245), predominantly in the middle territory (94/245). Deployment in zone 0–1 ( p  = .026), placement of a branched or fenestrated endograft ( p  = .038), a proximal endoprosthesis diameter ≥ 40 mm ( p  = .038), and an urgent procedure ( p  = .005) were significantly associated with the presence of SBI on univariable analysis, while urgent procedure was found to be an independent predictor on multivariable analysis (binary logistic regression) ( p  = .002). Conclusion: SBI following endovascular repair of the aortic arch is frequent, although there were no clinical strokes. Innovative strategies to reduce the risk of embolisation need to be developed.